Activation of Transcription Factor EB Is Associated With Adipose Tissue Lipolysis in Dairy Cows With Subclinical Ketosis - Yu, Hao; Gao, Xinxing; Loor, Juan J.; Jiang, Qianming; Fang, Zhiyuan; Hao, Xue; Shi, Zhen; Fan, Minghe; Chen, Meng; Li, Xinwei; Liu, Guowen; Wang, Zhe; et al. (Frontiers in Veterinary Science, 2022)
Excessive lipid mobilization for adipose tissue caused by severe negative energy balance is the pathological basis for subclinical ketosis (SCK) in dairy cows. In nonruminants, transcription factor EB (TFEB) was reported to play a role in the regulation of lipid catabolism, but its role in the control of lipolysis in the bovine is unknown. The present study aimed to determine whether the enhanced TFEB transcriptional activity contributes to lipolysis of adipose tissue in SCK cows, and to explore the possibility of establishing a therapeutic strategy by using TFEB as a target to control lipolysis. Thirty cows with similar lactation number (median = 3, range = 2 to 4) and days in milk (median = 6 d, range = 3 to 9) were selected into a healthy control (n = 15) and SCK (n = 15) group, and used for subcutaneous adipose tissue biopsies and blood sampling. Adipocytes from healthy Holstein calves were used as a model for in vitro studies involving treatment with 10 µM isoproterenol (ISO) for 0, 1, 2 and 3 h, 250 nM of the TFEB activator Torin1 for 3 h, or used for transfection with TFEB small interfering RNA for 48 h followed by treatment with 10 µM ISO for 3 h. Compared with healthy cows, adipose tissue in SCK cows showed increased lipolysis accompanied by enhanced TFEB transcriptional activity. In vitro, ISO and Torin1 treatment increased lipolysis and enhanced TFEB transcriptional activity in calf adipocytes. However, knockdown of TFEB attenuated ISO-induced lipolysis in adipocytes. Overall, these findings indicated that enhanced transcriptional activity of TFEB may contribute to lipolysis of adipose tissue in dairy cows with SCK. The regulation of TFEB activity may be an effective therapeutic strategy for controlling overt lipolysis in ketotic cows.